Biopsy findings in cases of rejection of liver allograft. Issue 12 (December 1985) - Hubscher, S G; Clements, D; Elias, E; McMaster, P
Abstract : Features of rejection were found in 21 needle biopsies obtained from seven patients after liver transplantation. Wedge biopsies taken peroperatively were used as a baseline for comparison. Rejection was diagnosed by excluding other known causes of graft dysfunction using appropriate methods. In cases in which these criteria were fulfilled a consistent picture of rejection was seen, and this was useful in clinical management. Two features constantly present in cases of acute rejection were: a dense mixed portal inflammatory infiltrate; and polymorphonuclear infiltration of biliary epithelium.